Fear of coronavirus: gender differences occur in Indonesia - Tika Antya Sari; Yulia Aryiza; Adi Cilik Pierewan; Yoga Setyo Wibowo (Universitas Negeri Padang, 2021)
The purpose of this study was to comply with the differences in the level of fear of COVID-19 between men and women in Indonesia. This research method is quantitative. The number of participants in this study was 131 people (59 men and 71 women). The criteria in this study were Indonesians who wanted to participate in this research and complete all of the existing questionnaires. This research uses the Fear of COVID-19 Scale instrument with 7 question items that have been translated into Indonesian. Testing the data using the independent t-test to see differences in the level of fear between genders. The results of this study are that women tend to experience more fear due to COVID-19 than men. Women feel traumatized and stressed by the presence of COVID-19. COVID-19 makes women's mood low and feels hyper-arousal.